Assessment of color, aroma, and selected physico-chemical properties of muscovado marketed by Panay fair trade center - Maghanoy, Jobelle V.
The study involved the assessment of color, aroma, moisture content, water activity, proximate composition and filth content of muscovado by the Panay Fair Trade Center (PFTC).